A dynamic compensator for in-domain control of Burgers' equation. Issue 7 (3rd July 2021) - Yang, Kaijun; Zhu, Guchuan
Abstract : This paper addresses the problem of output regulation control of a Burgers' equation under pointwise in-domain actuation. A dynamic compensator that generates the in-domain control is developed for output regulation of the considered system. A nonlinear boundary feedback control is used to ensure the closed-loop stability of the Burgers' equation. The proposed control scheme is implemented by means of Adomian decomposition method and flatness-based trajectory planning. A numerical simulation study is carried out, and the obtained results demonstrate the efficiency and effectivity of the proposed approach.